Integrating innovation and competency-based education in the development of a new direct-entry master of science in nursing program. - Moore, Wendy; Palerino, Andrea; Pawloski, Katie (Journal of Professional Nursing, 2024)
There has been a call for nursing programs to shift to Competency-based education (CBE). Competency-based education has numerous benefits in nursing education. A curriculum that includes both concepts and competencies helps students and stakeholders understand what new nurse graduates will be able to do with the knowledge they construct throughout the program. Competency-based education is student-centered, flexible, and dependent on students actively engaging in their learning. A small faculty team developed a new direct-entry MSN program, based on essential components of CBE. This article describes the process of incorporating CBE into the development of the program, as well as challenges and barriers to fully implementing CBE into the curriculum. • It is expected by CCNE that nursing programs shift to a model of competency-based education • A new direct-entry MSN program was developed based on essential components of competency-based education • Challenges and barriers continue to exist to fully integrating competency-based education into the curriculum • Building a program based on competency-based education was rewarding for faculty and students